Survey of the Knowledge, Attitudes and Practice towards Antibiotic Use among Prospective Antibiotic Prescribers in Serbia - Olga Horvat; Ana Tomas Petrović; Milica Paut Kusturica; Dragica Bukumirić; Bojana Jovančević; Zorana Kovačević (MDPI AG, 2022)
The complex issue of antibacterial resistance (ABR) requires actions taken with the One Health approach, involving both human and veterinarian medicine. It can spread from animals to humans through the food chain or through direct contact. Health profession students, as the future antibiotic providers, can greatly impact antibiotic-related issues in the future. The study was conducted to evaluate knowledge, attitudes and practice of future antibiotic prescribers in relation to judicious use of antibiotics. This cross-sectional, questionnaire-based study was performed on 400 students of health professions who were allowed to prescribe antibiotics of the University of Novi Sad, Serbia. Students of medicine and students of dentistry showed a significantly higher knowledge score compared to students of veterinary medicine (p = 0.001). Multivariate regression identified predictors of adequate antibiotic knowledge: being a female student (B = 0.571; p = 0.020), higher grade average (B = 1.204; p = 0.001), students of medicine (B = 0.802; p = 0.006) and dentistry (B = 0.769; p = 0.026), and students who used a complete package of antibiotics during the last infection (B = 0.974; p = 0.001) or for the period recommended by the doctor (B = 1.964; p = 0.001). Out of the total sample, self-medication was reported among 42.8% of students. The identified predictors of self-medication were: more frequent (B = 0.587; p = 0.001) and irregular (B = 0.719; p = 0.007) antibiotic use, taking antibiotics until symptoms disappeared (B = 2.142; p = 0.001) or until the bottle was finished (B = 1.010; p = 0.001) during the last infection. It seems prudent to reevaluate the educational curricula regarding antibiotic use and ABR of prospective prescribers in Serbia.